The embedded carbon footprint of urban households in China and its evolution - Zhao, D.; Fan, J.; Guo, X.; Marinova, Dora; Wu, Y. (The Modelling and Simulation Society of Australia and New Zealand Inc., 2011)
This paper explores the embedded carbon footprint (ECF) that is associated with various activities of urban households in China. An input-output model for carbon emissions is constructed. Based on urban household data for the period of 2003-2009, we calculate individual ECF and analyze its structural evolution. The results of this analysis show that the total ECF emission intensity increases when an individual’s consumption is higher than 10000 yuan (which is the turning point). This implies that emission intensity increases with a luxury lifestyle whereas it is lower for lower-income households. As income continues to increase, China will continue to remain on a high carbon track. We hence suggest that, with increasing urban wealth there is a need for better policies, management and behavioural change in order to reduce the carbon emissions of households. This study provides some policy suggestions about establishing a carbon quota system to guide individual consumption.